2018
DOI: 10.1017/s1743921319003235
|View full text |Cite
|
Sign up to set email alerts
|

Review of asteroid-family and meteorite-type links

Abstract: The materials of large asteroids and asteroid families are sampled by meteorites that fall to Earth. The cosmic ray exposure age of the meteorite identifies the collision event from which that meteorite originated. The inclination of the orbit on which the meteoroid impacted Earth measures the inclination of the source region, while the semi-major axis of the orbit points to the delivery resonance, but only in a statistical sense. To isolate the sources of our meteorites requires multiple documented falls for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 9 publications
1
13
0
Order By: Relevance
“…(1992a) calculated an average CRE age of 31 ± 2 Ma for Uden. This age overlaps with cluster “C” defined by Jenniskens () in the CRE age histogram of LL chondrites (Marti and Graf ; Graf and Marti ; Scherer et al. ; Eugster et al.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…(1992a) calculated an average CRE age of 31 ± 2 Ma for Uden. This age overlaps with cluster “C” defined by Jenniskens () in the CRE age histogram of LL chondrites (Marti and Graf ; Graf and Marti ; Scherer et al. ; Eugster et al.…”
Section: Discussionsupporting
confidence: 64%
“…, ). Instead, Dishchii'bikoh was ejected from a larger body 11 Ma ago, part of cluster “A” defined by Jenniskens (). Until now, no two LL chondrite falls have been photographed that originated in the same collision event (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that Hamburg arrived to us also from the 3:1 resonance at a = 2.50 AU, but alternatively may have arrived to us via the 5:2 resonance at a = 2.82 AU. If Pribram and Hamburg originated from the same collision event, then orbital dynamics suggests it more likely originated from a source with an initial low ~1° inclined orbit, rather than a more highly inclined ~10° orbit (Jenniskens 2019). Inclinations from initial low‐inclined orbits tend to increase over time due to interactions with Earth (Jenniskens 2019).…”
Section: Resultsmentioning
confidence: 99%
“…). Meteoroids generated in the outer Main Belt tend to evolve into Jupiter‐crossing orbits and are ejected from the solar system, before their perihelion reaches Earth orbit, unless they have an inclination much higher than the Veritas family (Jenniskens ).…”
Section: Discussionmentioning
confidence: 99%
“…Meier et al (2016) suggested that the group of 3-10 Ma old meteorites originated from the 8.3 AE 0.5 Ma breakup of the Veritas family (Nesvorny et al 2003), but this family of asteroids is located in the outer Main Belt (Michel et al 2010). Meteoroids generated in the outer Main Belt tend to evolve into Jupiter-crossing orbits and are ejected from the solar system, before their perihelion reaches Earth orbit, unless they have an inclination much higher than the Veritas family (Jenniskens 2019).…”
Section: Collisional History and Origin Regionmentioning
confidence: 99%